Water issues in Colorado - Wolfe, Dick, author (Colorado State University. Libraries, 2011)
Abstract only. Dick Wolfe covers two separate areas within Colorado of interest to the Central Plains region.
Proceedings of the 23rd annual Central Plains irrigation conference
Presented at Proceedings of the 23rd annual Central Plains irrigation conference held in Burlington, Colorado on February 22-23, 2011.